Infantile restrictive cardiomyopathy: cTnI-R170G/W impair the interplay of sarcomeric proteins and the integrity of thin filaments - Cimiotti, Diana; Fujita-Becker, Setsuko; Möhner, Desirée; Smolina, Natalia; Budde, Heidi; Wies, Aline; Morgenstern, Lisa; Gudkova, Alexandra; Sejersen, Thomas; Sjöberg, Gunnar; Mügge, Andreas; Nowaczyk, Marc M.; et al. (PLOS ONE, 2020)
TNNI3 encoding cTnI, the inhibitory subunit of the troponin complex, is the main target for mutations leading to restrictive cardiomyopathy (RCM). Here we investigate two cTnI-R170G/W amino acid replacements, identified in infantile RCM patients, which are located in the regulatory C-terminus of cTnI. The C-terminus is thought to modulate the function of the inhibitory region of cTnI. Both cTnI-R170G/W strongly enhanced the Ca2+-sensitivity of skinned fibres, as is typical for RCM-mutations. Both mutants strongly enhanced the affinity of troponin (cTn) to tropomyosin compared to wildtype cTn, whereas binding to actin was either strengthened (R170G) or weakened (R170W). Furthermore, the stability of reconstituted thin filaments was reduced as revealed by electron microscopy. Filaments containing R170G/W appeared wavy and showed breaks. Decoration of filaments with myosin subfragment S1 was normal in the presence of R170W, but was irregular with R170G. Surprisingly, both mutants did not affect the Ca2+-dependent activation of reconstituted cardiac thin filaments. In the presence of the N-terminal fragment of cardiac myosin binding protein C (cMyBPC-C0C2) cooperativity of thin filament activation was increased only when the filaments contained wildtype cTn. No effect was observed in the presence of cTn containing R170G/W. cMyBPC-C0C2 significantly reduced binding of wildtype troponin to actin/tropomyosin, but not of both mutant cTn. Moreover, we found a direct troponin/cMyBPC-C0C2 interaction using microscale thermophoresis and identified cTnI and cTnT, but not cTnC as binding partners for cMyBPC-C0C2. Only cTn containing cTnI-R170G showed a reduced affinity towards cMyBPC-C0C2. Our results suggest that the RCM cTnI variants R170G/W impair the communication between thin and thick filament proteins and destabilize thin filaments.
Gesehen am 21.04.2020